Respuesta :
we know that
The x-intercept is the value of x when the value of the function is equal to zero.
in this problem we have
[tex]f(x)=3x^{2}-11x-4[/tex]
To find the x-intercepts equate the function to zero
[tex]3x^{2}-11x-4=0[/tex]
Group terms that contain the same variable, and move the constant to the opposite side of the equation
[tex]3x^{2}-11x=4[/tex]
Factor the leading coefficient
[tex]3(x^{2}-(11x/3))=4[/tex]
Complete the square. Remember to balance the equation by adding the same constants to each side
[tex]3(x^{2}-(11x/3)+(121/36))=4+(121/12)[/tex]
[tex]3(x^{2}-(11x/3)+(121/36))=(169/12)[/tex]
[tex](x^{2}-(11x/3)+(121/36))=(169/36)[/tex]
Rewrite as perfect squares
[tex](x-(11/6))^{2}=(169/36)[/tex]
square root both sides
[tex](x-(11/6))=(+/-)(13/6)[/tex]
[tex]x=(11/6)(+/-)(13/6)[/tex]
[tex]x=(11/6)+(13/6)=24/6=4[/tex]
[tex]x=(11/6)-(13/6)=-2/6=-1/3[/tex]
therefore
the answer is
The negative x-intercept is at [tex](-1/3,0)[/tex]
The positive x-intercept is at [tex](4,0)[/tex]
The negative x-intercept is (-1/3, 0) and the positive x-intercept is (4,0)
Intercepts
Given the expression 3x²-11x-4, the x intercept occur that the point where f(x) = 0.
The function will become 3x²-11x-4 = 0
factorising expressions
Factorize the result to have:
- 3x² -12x + x - 4 = 0
Group the function to have;
- (3x²-12x)+(x-4) = 0
Factor out the GCF
3x(x-4) + 1(x-4) = 0
(3x+1) (x-4) = 0
Get the x-intercepts
3x+1 = 0
x = -1/3
Hence the negative x-intercept is (-1/3, 0)
Also, x-4 = 0
x = 4
Hence the positive x-intercept is (4, 0)
Learn more on intercepts here: https://brainly.com/question/24212383